Thermal Behavior of Present and Future Iraqi Constructed Walls (An Experimental Study) - Ali Hasan, Atif (Anbar Journal of Engineering Science, 2012)
The object of this paper was determined the thermal behavior of present and future constructs Iraqi walls at Baghdad climate region (Latitude 33.2 °N) with or without (40) mm insulating materials. The study was carried out at day (21) July for East Orientation. The obtained results were tabulated in terms of over all heat transfer coefficient, weight of the wall per unit area, wall thickness, temperature difference between outside and inside wall face and the temperature difference between inside of the room and it’s inside wall surface through on. day hours and it’s average values.